Literature Study of Client Problems Psychoanalytic Criteria - Fatimatul Husna; Romauli Yulita; Astri Ichsan Syamrosa; Gusman Lesmana (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to describe the use of psychoanalytic counseling on clients. This research is a type of literature study where the writer looks for references from articles, books, and other references that are in accordance with the discussion of the research article material. The advantages of counseling include that clients can find out about what problems they are actually not aware of because this approach explores internal conflicts that occur within individuals and we as counselors help clients to understand the problem and find what is the cause of the problem and formalize it to the client so that the client one of the weaknesses of the psychoanalytic approach is that counseling with this approach is considered less efficient in terms of time and cost because the time needed in therapy is quite long and costs a lot of money because digging into the client's past cannot be done only by just one meeting and make the client become bored in the therapy process. The conclusion of this study is that in the psychoanalytic approach, human beings are basically deterministic, which is determined by psychic energy and self-experience. Therefore, in counseling and psychoanalytic therapy, it emphasizes the re-establishment of a healthy personality structure in clients, by raising things in the unconscious into consciousness.